2012
DOI: 10.1152/ajpcell.00386.2011
|View full text |Cite
|
Sign up to set email alerts
|

Soluble epoxide hydrolase expression in a porcine model of arteriovenous graft stenosis and anti-inflammatory effects of a soluble epoxide hydrolase inhibitor

Abstract: Synthetic arteriovenous (AV) grafts, placed between an artery and vein, are used for hemodialysis but often fail due to stenosis, typically at the vein-graft anastomosis. This study recorded T lymphocyte and macrophage accumulation at the vein-graft anastomosis, suggesting a role for inflammation in stenosis development. Epoxyeicosatrienoic acids (EETs), products of cytochrome P-450 epoxidation of arachidonic acid, have vasculoprotective and anti-inflammatory effects including inhibition of platelet activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 70 publications
3
22
0
Order By: Relevance
“…Previous work by our group has also shown that macrophage accumulation and cytokine expression are pronounced features of AVG stenosis and that a pharmacological inhibitor of sEH caused a significant decrease in release of monocyte-chemotactic protein-1 and TNF from lipopolysaccharide-stimulated human monocytes in vitro . [40] The data presented herein, together with previous works, suggest that sEH inhibition could be useful for the prevention of AVG stenosis by both targeting inflammation as well as cell migration.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Previous work by our group has also shown that macrophage accumulation and cytokine expression are pronounced features of AVG stenosis and that a pharmacological inhibitor of sEH caused a significant decrease in release of monocyte-chemotactic protein-1 and TNF from lipopolysaccharide-stimulated human monocytes in vitro . [40] The data presented herein, together with previous works, suggest that sEH inhibition could be useful for the prevention of AVG stenosis by both targeting inflammation as well as cell migration.…”
Section: Discussionsupporting
confidence: 52%
“…[40] These intriguing and promising data support the further investigation of oxylipids and sEH in AVG dysfunction.…”
Section: Introductionmentioning
confidence: 77%
“…10-0398). Peripheral blood mononuclear cells (PBMC) were isolated by an adherent method previously described[34]. The PBMC were cultured in 96-well culture plates (2.5 x 10 4 cells/0.3 cm 2 ) with fat/PGZ or fat/ROS culture conditioned media diluted in half with SFM media (Gibco Life Technologies, ThermoFisher Scientific) supplemented with 20% serum.…”
Section: Methodsmentioning
confidence: 99%
“…Lu et al [71] found apelin to have the opposite effect on MCP-1, stimulating its expression and secretion in HUVECs via c-Jun NH2-terminal kinase (JNK) and NF-κB. JNK [72,73] and NF-κB [73] have been described to stimulate MCP-1 in other cells, too ( Figure 2). Hence, further research will be needed to reconcile these data, as there can be other factors downstream of apelin/APJ signalling which affect the induction of MCP-1 expression.…”
Section: Monocyte Chemoattractant Protein-1mentioning
confidence: 99%